The relationship between ball speed and ball spin of serve in collegiate male tennis players - Takahashi, H.; Kashiwagi, R.; Okamura, S.; Murakami, S (Science and Racket Sports VI, 2019)
The purpose of this study is to clarify the relationship between ball speed and ball spin of serve in collegiate male tennis players. Participants of this study was 14 male collegiate tennis players. They were divided into two groups: high ranked players (HRP) and low ranked players (LRP). Trackman tennis radar was used to collect data of experimental matches by participants. As a result, ball speed of 1st serve of HRP (157.7±16.7km/h) was significantly faster than LRP (153.0±14.5km/h). Ball spin of 1st serve was not significantly different between HRP (2462±925rpm) and LRP (2332±823rpm). Additionally, it found that HRP occurred faults in high speed and low spin range, and LRP showed faults even in low speed and high spin range from distribution of ball speed and ball spin of 1st serve. We concluded that HRP had different technique of 1st serve in high spin range. HRP could reduce errors in 1st serve because of high spin rate.